Al-Mawāhib/Los Dones (1945-1960). The Unofficial Embassy of the Arab-ʿAlawī Community in Argentina - Köster, Katrin (Oriente moderno, 2025)
This article analyses the first years of the cultural journal al-Mawāhib/Los Dones (Talents, Tucumán 1945-1960), one of the first periodicals published in the Latin American diaspora by an ʿAlawī editor, Yūsuf al-Ṣārmī (d. 1986). Conceptualizing periodicals as tools of community formation that are deeply embedded in social practices and networks, this article argues that al-Mawāhib formed three overlapping but distinct communities: it acted as a material link between ʿAlawīs in Syria and in the diaspora, presented itself as the unofficial embassy of a pan-Arab network of intellectuals, and referred to Arab heritage to evoke an all-encompassing Arab umma. The article thus demonstrates how a journal that had emerged from a minoritarian reform network contributed to shaping pan-Arab reform discourses and endeavours and could indeed act as an "unofficial embassy". In doing so, the case study challenges simplified centre-periphery dichotomies, highlights the translocal nature of Arab print-networks, and showcases the significant role a seemingly peripheral medium could play in the Islamicate world in the mid-20th century.